Ibuprofen induced intestinal bleeding presenting as Crohn`s in a collegiate baseball player: A case report - Warner, B. J.; Gallegos, D. M.; Cage, H. M.; Cage, S. A. (Journal of Athletic Training, 2019)
Background: A 22-year-old collegiate baseball player reported to the athletic training staff complaining of persistent low back pain and associated muscle spasm. The patient had initially noticed the pain during the acceleration portion of his pitching motion, but had begun to experience pain during all phases of pitching along with daily activities. The patient stated that he had dealt with low back pain during high school, but had always managed it with rest, OTC ibuprofen, and regular chiropractic adjustments. Further evaluation revealed palpable spasm along the erector spinae muscle at the lower thoracic and lumbar levels, palpable pain at the L4-L5 levels of the lumbar vertebrae, pain with active lumbar extension, and general abdominal muscle weakness. Other than the previously mentioned low back pain, no other pertinent medical history was reported. Differential Diagnosis: Facet syndrome, spondylolysis, spondylolisthesis, erector spinae strain. Treatment: During the initial phase of treatment and rehabilitation, the patient's symptoms were addressed with ice, motor transcutaneous electrical nerve stimulation, cupping therapy, and stretching. As the patient's symptoms began to subside, he began a therapeutic exercise program designed to address core and pelvic instability and weakness. After two weeks of treatment, the patient continued to experience his symptoms with little relief. At this time, the patient was referred to the team physician for further evaluation. The team physician's exam was consistent with facet syndrome, and an MRI was ordered. MRI revealed moderate swelling around the facet joints at the L4-L5 levels, absent of other structural abnormalities. Having obtained the results of the MRI, the patient underwent two more weeks of rehabilitation, but was unable to progress to return to play. Due to the length of time the patient had remained symptomatic, the decision was made to refer him to a local pain management specialist. After a consultation, the patient consented to a course of cortisone injections into his facet joints. After undergoing three injections over the course of two months, the patient was still not experiencing signifi cant relief. By the time the season had ended, the patient was given a home exercise program prior to his returning home for the summer. During a routine visit, the patient's primary care physician ordered a CT scan to further evaluate the patient's lower back. CT scan revealed fi ndings consistent with Crohn's Disease. With the new diagnosis, the patient began regular infusions of infl iximab which provided relief that would subside within three to four weeks of infusion. The patient continued treatment with infl iximab infusions upon returning to school for the fall semester, but was hospitalized over winter break with increased intraabdominal pain. A proctoscopic exam found that the patients intestines had been signifi cantly damaged due to long term use of ibuprofen. With this third diagnosis, infl iximab infusions were discontinued and the patient was instructed to cease ibuprofen usage. Throughout the spring semester the patient's symptoms continued to improve until he was ultimately able to return to physical activity pain free. Uniqueness: While damage to the intestines through ibuprofen consumption has been well documented in literature, this case describes a situation in which a patient's intestinal damage mimicked the symptoms of both facet syndrome and Crohn's Disease. The presence of infl ammation at the facet joints was a confounding sign that complicated the diagnostic process and delayed the administration of appropriate care. Conclusions: When treating a patient with a condition that is not responding to conservative treatment, it is paramount that the clinician exhaust all diagnostic options to determine the underlying pathology. Instances conditions presenting with signs and symptoms mirroring other conditions make appropriate follow-up and confirmation of diagnosis crucial to the healthcare process.